PSA-IgM and iXip in the diagnosis and management of prostate cancer: clinical relevance and future potential. A review. - Maestroni, Umberto; Cavalieri, Domenico Maria; Campobasso, Davide; Guarino, Giulio; Ziglioli, Francesco (Acta Biomedica Atenei Parmensis, 2022)
The Prostate Specific Antigen (PSA) is the first filter in the diagnosis of prostate cancer. Unfortunately, it is organ-specific but not cancer-specific. In addition, some prostate cancers are not clinically-significant and their diagnosis and treatment may lead to overdiagnosis and overtreatment. For these reasons, other markers have been proposed in the last years, such as PCA3 and PHI, but none of these are currently used in the clinical practice on large scale. In the last decade, PSA-IgM and the algorithm iXip have emerged for the diagnosis of prostate cancer and showed to perform well in decreasing the detection of clinically-insignificant prostate cancer and in reducing the number of unnecessary prostate biopsies. This review focuses on data reported in the literature on PSA-IgM and iXip as well as on the future perspectives of their usage in the clinical practice on large scale.